Alternative Media, Alternative Voices? A Quantitative Analysis of Actor Diversity in Alternative and Mainstream News Outlets. Issue 2 (7th February 2022) - Buyens, Willem; Van Aelst, Peter
Abstract: Alternative news media are largely independent players in the news environment, which allows them to publish more alternative, and possibly more radical, news content. Do they utilise their independence to display actors that are underrepresented in the mainstream news? And does it affect the actor diversity in their news coverage and the journalistic environment as a whole? This study scrutinises the differences in actor diversity and actor presentation in articles published by alternative and mainstream news media to gauge if alternative media are more one-sided and if they contribute to the external actor diversity of the news environment. We analyse a sample of news articles on migration and social affairs published by two mainstream media and four alternative outlets. Despite limited differences in article-level actor diversity between alternative and mainstream news media, our findings highlight that right-wing and left-wing alternative media exploit their editorial independence differently to highlight other actor categories. Left-wing alternative news media present more civil society actors, while right-wing alternative news outlets pay more attention to right-wing politicians and parties. Thus, alternative news media are not that different in terms of internal actor diversity, but they modestly advance the external actor diversity in the news environment.